Pengaruh Pemahaman Akuntansi Terhadap Kepatuhan Wajib Pajak UMKM - Clara Putri; Nur Aliah (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This research aims to analyze the effect of accounting and taxation understanding on the compliance of MSME taxpayers at the East Medan Tax Office (KPP). This study uses a quantitative approach with a Casual Comparative Research design, utilizing primary data obtained through questionnaires from 98 MSME respondents. Data analysis was conducted through validity, reliability, normality, multicollinearity, and multiple linear regression tests using SPSS version 25. The results show that both accounting and tax understanding have a positive and significant effect on taxpayer compliance. Simultaneously, these two variables explain 30.5% of the variation in MSME taxpayer compliance, while the rest is influenced by other factors, such as business experience, legal knowledge, and tax awareness. These findings confirm that a good understanding of taxation can improve the compliance of MSMEs in carrying out their tax reporting and payment obligations. Meanwhile, an understanding of accounting needs to be supported by the application of proper financial recording to avoid misinterpretation. Based on these findings, this study recommends the implementation of structured tax training, simple accounting education for MSMEs, and further research to identify additional factors that influence tax compliance. The results of this study are expected to serve as a reference for the Directorate General of Taxes and MSME actors in increasing tax awareness and compliance.